ANTIMICROBIAL AND IMMUNE FACTORS IN THE DIAGNOSIS AND PROGNOSIS OF NEONATAL SEPSIS - Kerimova, N.T.; Efendiyev, A.M. (World of Medicine and Biology, 2024)
The purpose of the study was to determine the clinical significance of antimicrobial peptides, pro- and anti-inflammatory cytokines in sepsis in newborns. In the course of this study, the role of endotoxin and cytokines in early diagnosis of sepsis was also studied. The determination was carried out using the standard method of solid-phase (“sandwich” version) enzyme-linked immunosorbent assay on an automatic analyzer “Elaysis Uno” (Germany). The study included 72 newborns diagnosed with sepsis, early neonatal sepsis (n=15), late neonatal sepsis (n=50) and control group (n=7). The changes of the levels of endotoxin, pro-inflammatory and anti-inflammatory cytokines in the blood serum depends on the dynamics of septic process were revealed Thus, the determination of endotoxin and cytokines makes it possible to identify the development of sepsis and predict its severity and course in premature infants of various gestational ages.
Keywords: sepsis; preterm and term infants; endotoxin; cytokines